Pengaruh Artificial Intelligence (AI) Terhadap Kemampuan Mahasiswa dalam Menyampaikan Presentasi di Depan Kelas - Choirunisa, Safira; Sihotang, Cita Uli; Hulu, Kristian Irwan; Sembiring, Katarinna; Sinaga, Laura Chesla; Waruwu, Ferdianus; Macap, Nurul Aulia (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The development of Artificial Intelligence (AI) has significantly impacted higher education, particularly in improving students' presentation skills in the classroom. Various AI-based applications, such as ChatGPT, Gemini, and Copilot, assist students in gathering information, organizing presentation materials, creating presentation slides, and practicing public speaking. This study aims to analyze the influence of AI on students' ability to deliver presentations in front of the class. The research employs a library research method by reviewing relevant journals, books, and scientific articles. The findings indicate that AI can enhance the quality of presentation materials, increase students' confidence, improve communication skills, and support more effective information delivery. However, excessive reliance on AI may reduce students' critical thinking and independent problem-solving abilities. Therefore, AI should be utilized wisely as a learning support tool rather than as a substitute for students' intellectual and analytical capabilities. The study concludes that AI has a positive impact on students' presentation performance when used appropriately and responsibly.